Isometric muscle force, rate of force development and knee extensor neuromuscular efficiency asymmetries at different age groups - Helen L Schimidt; Álvaro S Machado; Marco A Vaz; Felipe P Carpes (Universidade Federal de Santa Catarina, 2014)
The aim of this study was to evaluate force, rate of force development and knee extensor neuromuscular efficiency asymmetries in children, adults and elderly. Each subject performed maximal isometric voluntary contractions (MIVC) and submaximal trials (15% and 30% MIVC). Maximal force, rate of force development (RFD) and neuro-muscular efficiency were evaluated and compared between groups and between preferred and non-preferred lower limb. Children (mean age 8.4, SD 0.7 yrs), female adults (mean age 23.2, SD 3.5 yrs) and elderly (mean age 65.9 SD 7.0 yrs) were evaluated. RFD was higher in young adults, and similar between children and elderly. Neuromuscular efficiency decreased significantly with aging (P<0.05). Inter-limb asymmetries were observed for force and RFD in favor of the preferred lower limb in the elderly (P<0.05). Force and RFD asymmetries in the elderly are supported by the right hemisphere-aging model contribut-ing to increased motor asymmetries. It was suggested that both physical assessment and training in the elderly should consider asymmetries that apparently are inherent to the aging process. A simple protocol for maximal and submaximal force assessment may be useful for delineating impairments in force and power in the elderly.